2011
DOI: 10.5194/angeo-29-2031-2011
|View full text |Cite
|
Sign up to set email alerts
|

Substorms during different storm phases

Abstract: Abstract. After the deep solar minimum at the end of the solar cycle 23, a small magnetic storm occurred on 20-26 January 2010. The Dst (disturbance storm time) index reached the minimum of −38 nT on 20 January and the prolonged recovery that followed the main phase that lasted for about 6 days. In this study, we concentrate on three substorms that took place (1) just prior to the storm, (2) during the main phase of the storm, and (3) at the end of the recovery of the storm. We analyse the solar wind condition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
12
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 39 publications
6
12
1
Order By: Relevance
“…Considering the median index values, the substorm recovery phase is typically as intense as the expansion phase, and thus plays an important role in dissipating the storm energy, even when the role of the expansion phase is emphasised during storm-times. This is in agreement with the results of an event study by Partamies et al (2011). Yet, there are a lot of unanswered questions about substorm recovery phase processes.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Considering the median index values, the substorm recovery phase is typically as intense as the expansion phase, and thus plays an important role in dissipating the storm energy, even when the role of the expansion phase is emphasised during storm-times. This is in agreement with the results of an event study by Partamies et al (2011). Yet, there are a lot of unanswered questions about substorm recovery phase processes.…”
Section: Discussionsupporting
confidence: 91%
“…In this light, it is not surprising that the case studies found in the literature are so different from each other. In fact, the substorm phase lifetimes during different storm phases reported by Partamies et al (2011) are much longer than the statistical values found in this study. The largest range of lifetimes is covered by the durations of substorm recovery phases, from 11 min of the single-cycle substorm recoveries during the storm main phases to the 37 min of the multi-cycle substorm recoveries during the storm recovery phases (Table 7).…”
Section: Discussioncontrasting
confidence: 73%
See 1 more Smart Citation
“…Geomagnetic storms and substorms are important space weather phenomena and an intensely active space weather research topic. Many investigators have studied geomagnetic storms and substorms (e.g., Akasofu and Chapman, 1963;Lakhina et al, 2006;Russell et al, 1974;Partamies et al, 2011). It is well known that substorms can occur during super storms and intense storms, or even independently of storms (Hajra et al, 2016;Partamies et al, 2013;Tsurutani et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Many researchers studied this problem using both satellite data and ground-based data (IMAGE magnetometers data, AL, AU indexes, data of auroras) (e.g. Tsurutani et al 2004;Milan et al, 2008Milan et al, , 2009Partamies et al, 2011;Despirak et al, 2009Despirak et al, , 2011. It is known that as a result from storm investigations, the various phases of the storm were defined.…”
Section: Introductionmentioning
confidence: 99%